Índices de sustentabilidade hídrica com base na pegada hídrica cinza em nível de bacia hidrográfica - Masteghin, Ligia Tambasco (2019)
The objective of this work was to establish a methodology that would allow a better understanding of the management of water resources from the point of view of the water sustainability of a water system. For this, a method was proposed for the calculation of the subsidy flow. This methodology can be applied in any river basin that has information on the discharge of pollutant loads in its water systems. In this study, the methodology was applied to the Paraíba do Sul River Basin. The subsidy flow was correlated with minimum reference flows through the Water Sustainability Indices (WSI). Some future scenarios and their impacts on the management of water resources in the studied basin were evaluated. The proposition of the subsidy flow model that involved dilution factors related to effluent concentrations (BOD) passing through the sewage treatment station and those from raw sewage was able to estimate the flow rates required for dilution, for the two scenarios analyzed , current and future (2013 and 2035). The correlation of the subsidy flows with the minimum reference flows, through WSI, showed that the future scenario (2035) improves the physical, chemical and biological conditions of most water bodies, since 70.5% of the (WSH<1) when compared to the current scenario (2013), where this percentage is 55%. The best alternative evaluated concerns the alteration of the original efficiencies, of the Sewage Treatment Stations (STS) already existing in the system, and of the STS created to treat all the raw sewage, since, after such changes, considering the current scenario, in only a watercourse (approximately 1%), the condition of the subsidy flow is lower than the reference flow rate, while for the future scenario, 100% of the rivers and streams will meet these conditions. Thus, the subsidy flow that has its methodology based on the gray water footprint can be considered as an instrument of water resources management, used to evaluate impacts and situations of degradability of the aquatic environment, becoming important in the decision making for prevention or remediation of environmental impacts.